PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN LKPD TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA DI SMA - Wahyuni, Peni; Astuti, Dwi; Ijuddin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know the effect of problem based learning model LKPD assisted on student’s problem solving ability in SPLTV matter. Research method used is comparative form of pseudo-experiment with posttest only, non-equivalent control group design. There are two sample class, experiment class with 27 students and control class with 30 students. Based on Independent Sample T Test result obtained significant value 3,35 which shows the difference between student’s problem solving ability taught by problem based learning model and conventional learning. Based on the indicator obtained that student taught by problem based learning model have higher problem solving abilitythan student taught by conventional learning. The effect size value is 0,86 and categorized high. The conclusion is there is better influence on student’s problem solving ability taught by problem based learning model in SPLTV matter at school. Keyword: Problem Based Learning, LKPD, Problem Solving Ability